2022
DOI: 10.1136/bmjopen-2022-064834
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, education and health insurance coverage among women of reproductive ages in the Democratic Republic of the Congo: a cross-sectional and multilevel analysis

Abstract: ObjectiveTo investigate inequalities of health insurance coverage (outcome) at subnational level, and the effects of education and poverty on the outcome.DesignSecondary analysis of Demographic and Health Surveys. The outcome variable was health insurance ownership.SettingThe Democratic Republic of the Congo.SubjectsWomen aged 15–49 years (n=18 827).ResultsFindings indicated significant spatial variations of the health insurance ownership which ranged from 1.2% in Bandundu and Kasaï Oriental to 15.5% in Kinsha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The results showed that approximately 4% of male and female respondents had health insurance coverage in the DRC with hardly any difference between the genders which is a very low rate even for African standards. This result is consistent with the findings of Dimbuene et al (2022) who reported a low HI uptake of 5% for women of reproductive age in the DRC. Shao et al (2022) also confirmed a low HI coverage in the DRC of 2.8%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that approximately 4% of male and female respondents had health insurance coverage in the DRC with hardly any difference between the genders which is a very low rate even for African standards. This result is consistent with the findings of Dimbuene et al (2022) who reported a low HI uptake of 5% for women of reproductive age in the DRC. Shao et al (2022) also confirmed a low HI coverage in the DRC of 2.8%.…”
Section: Discussionsupporting
confidence: 93%
“…Our results corroborate the findings of Adebayo et al (2015) who found that wealthier households and individuals were more likely to own HI than poor individuals in countries such as Cameroon, Burkina Faso, and Nigeria. In the same context as the DRC, Dimbuene et al (2022) found similar results demonstrating that women of reproductive ages living in better‐off households had higher chances of being covered by an HI compared to those from poor households. In their study, Doris et al (2022) revealed that households in the lowest income quintile were 19% less likely to own HI than those in the wealthier group.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Similarly, Seidu et al [10] found that being in a polygamous relationship exacerbated the risk of MHRFB in SSA. Also, studies have identified poverty, substance use, marital status, post-traumatic stress disorder, and conventional gender role belief as factors associated with MHRFB [11][12][13].…”
Section: Introductionmentioning
confidence: 99%